2023
DOI: 10.3390/ijms24044235
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel-Based Pre-Clinical Evaluation of Repurposed FDA-Approved Drugs for AML

Abstract: In vivo models of acute myeloid leukemia (AML) are low throughput, and standard liquid culture models fail to recapitulate the mechanical and biochemical properties of the extracellular matrix-rich protective bone marrow niche that contributes to drug resistance. Candidate drug discovery in AML requires advanced synthetic platforms to improve our understanding of the impact of mechanical cues on drug sensitivity in AML. By use of a synthetic, self-assembling peptide hydrogel (SAPH) of modifiable stiffness and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Despite the superior physiological relevance of the 3D culture, reliable 3D leukemia CME models remain scarce. Recently, James et al (James et al, 2023) reported a 3D cell culture model with the leukemic cells embedded in an external peptide-based hydrogel mimicking the properties of the ECM. Authors used multi-well plates to study the responses of various types of leukemic cell lines embedded in a peptide hydrogel layer to several anti-cancer drugs supplied from the external media.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the superior physiological relevance of the 3D culture, reliable 3D leukemia CME models remain scarce. Recently, James et al (James et al, 2023) reported a 3D cell culture model with the leukemic cells embedded in an external peptide-based hydrogel mimicking the properties of the ECM. Authors used multi-well plates to study the responses of various types of leukemic cell lines embedded in a peptide hydrogel layer to several anti-cancer drugs supplied from the external media.…”
Section: Discussionmentioning
confidence: 99%
“…In a preclinical evaluation, a synthetic, self-assembling peptide hydrogel (SAPH) of variable stiffness and composition was utilized to screen repurposed and FDA-approved drugs for acute myeloid leukemia (AML). 62 It had acted as a 3D model of the bone marrow niche. The candidate drugs were salinomycin (antibacterial), vidofludimus (multiple sclerosis drug), and atorvastatin (anticholesterol drug).…”
Section: Drug Deliverymentioning
confidence: 99%
“…Apart from drug delivery, hydrogels have emerged as 3D surrogate platforms in various disease models and applications like scaffolds and cell transplantation. In a preclinical evaluation, a synthetic, self-assembling peptide hydrogel (SAPH) of variable stiffness and composition was utilized to screen repurposed and FDA- approved drugs for acute myeloid leukemia (AML) . It had acted as a 3D model of the bone marrow niche.…”
Section: Polymeric Platformsmentioning
confidence: 99%
“…In vivo tests represent a determinant step for hydrogel applications. Interdisciplinary studies for hydrogel design, characterization, and in vitro investigations [55,92,116,189,380,381], along with access to preclinical and clinical studies to ensure safety and efficacy of new materials [98,271,[382][383][384][385], will accelerate the application of new concepts and revolutionary materials. Last but not least, education regarding the protection of nature, which generously offers us a variety of biomolecules, must be promoted beyond the academic framework.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%